2020
DOI: 10.3389/fpsyt.2019.00986
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-Step, an E-Mental Health Intervention for Depression: A Mixed Methods Pilot Study From Lebanon

Abstract: Background: E-mental health is an established mode of delivering treatment for common mental disorders in many high income countries. However, evidence of its effectiveness in lower income countries is lacking. This mixed methods study presents lessons learned and preliminary data on the feasibility of a minimally guided e-mental health intervention in Lebanon. The aim was to pilot test Step-by-Step, a WHO guided e-mental health intervention, and research methods prior to future, controlled testing.Methods: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 23 publications
(22 reference statements)
5
42
1
Order By: Relevance
“…The latter group has been of particular interest, with many studies assessing the mental health needs of Syrians and other refugees who fled their nations to Lebanon (E. Karam et al, 2016; Kerbage et al, 2020; Yassin, Taha, Ghantous, Atoui, & Forgione, 2018). Lastly, many mental health interventional activities are being studied in these groups (Dirani, Raad, & Akoury‐Dirani, 2018; Harper Shehadeh et al, 2020; Kaplan, El Khoury, Lize, Wehbe, & Mokhbat, 2019; Noubani et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The latter group has been of particular interest, with many studies assessing the mental health needs of Syrians and other refugees who fled their nations to Lebanon (E. Karam et al, 2016; Kerbage et al, 2020; Yassin, Taha, Ghantous, Atoui, & Forgione, 2018). Lastly, many mental health interventional activities are being studied in these groups (Dirani, Raad, & Akoury‐Dirani, 2018; Harper Shehadeh et al, 2020; Kaplan, El Khoury, Lize, Wehbe, & Mokhbat, 2019; Noubani et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Internet and mobile-based interventions appear to be promising for potential scalability and may therefore contribute to narrow the worldwide treatment gap, particularly among “hard-to-reach populations” such as culturally diverse populations (e.g., Abi Ramia et al, 2018 ; Atallah et al, 2018 ; Burchert et al, 2019 ; Carswell et al, 2018 ; Cuijpers et al, 2008 ; Garabiles et al, 2019 ; Hedman et al, 2012 ; Kayrouz et al, 2018 ; Muñoz, 2010 ; Sijbrandij et al, 2017 ; Wang et al, 2013 ). Through large randomized controlled trials (RCTs) and pilot studies, several research groups seek to examine the effectiveness of culturally adapted online-interventions for treating common mental disorders such as depression, anxiety or post-traumatic stress disorder (PTSD) and culturally shaped concepts of distress in different indigenes cultures and their diaspora ( Harper Shehadeh et al, 2020 ; Kayrouz et al, 2015a , Kayrouz et al, 2016b ; Reich et al, 2019 ; Salamanca-Sanabria et al, 2018 , Salamanca-Sanabria et al, 2020 ; Sidani et al, 2018 ; Slobodin et al, 2018 ; Ünlü Ince et al, 2013 ; van't Hof et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to small sample sizes and high attrition rates in the pilot studies ( Harper Shehadeh et al, 2020 ; Kayrouz et al, 2016b , Kayrouz et al, 2016a ; Salamanca-Sanabria et al, 2020 ), only cautious assumptions can be made concerning statistically substantial effects on the reduction of distressing symptoms. However, the largely positive results on feasibility and acceptability of the mentioned studies seem promising, emphasizing the need for culturally adapted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The SbS program with minimal guidance has been piloted among Syrian refugees and local population in Lebanon [ 23 ]. A qualitative evaluation of the SbS program in Germany found that the Syrian refugees accepted the digital intervention and perceived the potential impact of the intervention on their mental health [ 24 ].…”
Section: Current Studymentioning
confidence: 99%
“…In order to utilize this trial design, the intervention should be supported by at least indirect effectiveness evidence and pose minimal risk to participants [ 29 ]. These characteristics are found in the WHO SbS program, since it was trialed on Syrian refugees, who share similar background as immigrants with OFWs in Macao, and showed no perceived risks for its application [ 23 ], and the evidence from the cultural adaptation and initial feasibility study conducted among OFWs in Macao.…”
Section: Current Studymentioning
confidence: 99%